A força de Eros em Gabrielle Coco Chanel: um estudo acerca da positividade na histeria feminina - Nobre, Thalita Lacerda (2012)
This present work brings a doctoral thesis that in some cases of hysteria, the phallicity, when articulates with Eros force, promotes a sublimatory condition called me by the condition of positivity. The interest for this study began in my practice in both private practice and in public service desk, where I observed that some patients who considered carrying hysterical neurosis, had a tendency to sublimation. This mode of pulsional satisfaction employed by these patients allowed their psyches to leave making use of phobic symptoms or conversive, besides bringing social recognition from the cultural establishment. In order to deepen these clinical questions, I used as an object of study French designer Gabrielle "Coco" Chanel, who can be recognized until the current days as one of the most creative designers. Her revolutionary creations have allowed the woman of the twentieth century a freedom to be in the public space, from the changes that were taking place in the private sphere. Besides comfortable clothing that guaranteed elegance and appreciation of female body, Chanel created a specific haircut model, created pants, perfumes, fake jewelrys and exclusive shoes that bear her name until the current days. Her life history is marked by suffering and rejections, and some hysterical symptoms were impossible to overcome, however, which can be obtained in this research, as a result, is that her sublimatory condition allowed to remain productive until the last days of her life, valuing and being valued by the production, which made her symptoms remained in a secondary condition, that is, they do not incapacitated her